Beyond belief : [large type] : the secret Gospel of Thomas - Pagels, Elaine H., 1943- (Random House Large Print, 2003)
[This book] explores how Christianity began by tracing its earliest texts, including the secret Gospel of Thomas, rediscovered in Egypt in 1945 ... [The author explores] historical and archeological sources to investigate what Jesus and his teachings meant to his followers before the invention of Christianity as we know it ... [She] compares such sources as Thomas' gospel ... with the canonic texts to show how Christian leaders chose to include some gospels and exclude others from the collections we have come to know as the New Testament. To stabilize the emerging Christian church in times of devastating persecution, the church fathers constructed the canon, creed, and hierarchy--and, in the process, suppressed many of its spiritual resources.-Dust jacket.